2022
DOI: 10.3390/ijerph19053103
|View full text |Cite
|
Sign up to set email alerts
|

Basic Psychological Needs at Work: Their Relationship with Psychological Well-Being and Healthy Organisational Outcomes with a Gender Perspective

Abstract: The aim of the study is to evaluate the mediating role of psychological well-being between the satisfaction/frustration of Basic Psychological Needs (BPN) and Healthy Organisational Outcomes, with a gender perspective. In a sample of 565 workers (65% women, response rate 72%) from two Colombian food companies, using Multigroup Structural Equation Models to test the invariance among gender, the study hypotheses were partially supported. The results show that: (1) psychological well-being fully mediates the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
3
1
Order By: Relevance
“…Furthermore, no gender differences seemed to emerge from expressions of autonomy. This differs from prior workplace studies, which reported higher satisfaction of autonomy needs for men than women in the food industry [19] as well as in another male-dominated fieldinvestment banking [16]. However, academia is already such a high-autonomy job that this might overcome effects of gender bias, at least with respect to autonomy.…”
Section: Research Questions #2 and #3contrasting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, no gender differences seemed to emerge from expressions of autonomy. This differs from prior workplace studies, which reported higher satisfaction of autonomy needs for men than women in the food industry [19] as well as in another male-dominated fieldinvestment banking [16]. However, academia is already such a high-autonomy job that this might overcome effects of gender bias, at least with respect to autonomy.…”
Section: Research Questions #2 and #3contrasting
confidence: 93%
“…Unfortunately, the study was not able to discern whether managers gave women less autonomy support than men or that women simply perceived the same support to be less conducive to autonomy. A similar result was found in a study of workers in the food industry where men reported less frustration of autonomy needs than women [19]. Like the study of investment bankers, it was unclear whether this finding was a result of the way managers treat their employees or of the way employees perceive their managers.…”
Section: Does Gender Matter With Regard To Basic Psychological Needs ...supporting
confidence: 54%
See 2 more Smart Citations
“…Similar positive outcomes have been demonstrated in a wide range of workplace studies in the twenty-first century. For example, satisfaction of the three basic psychological needs has been clearly linked to greater job satisfaction for employees working in psychiatric facilities [17], better performance evaluations and well-being at work in the high stress world of investment banking [18], greater overall psychological health in government organizations [19], more hours and greater engagement among volunteers at an animal shelter [20], and greater well-being, job performance, and affective commitment to the job for food industry workers [21]. Further, the mere perception that managers support the basic psychological needs of their subordinates has been associated with reduced somatic system burden (i.e., physical symptoms that have no medical explanation but are related to poor quality of life and disability) [22].…”
Section: How Are Basic Psychological Needs Relevant At Work?mentioning
confidence: 99%